An Evaluation of Curcumin-Encapsulated Chitosan Nanoparticles for Transdermal Delivery - Nair, Rajesh Sreedharan; Morris, Andrew; Billa, Nashiru; Leong, Chee-Onn (AAPS PharmSciTech, 2019)
Curcumin-loaded chitosan nanoparticles were synthesised and evaluated in vitro for enhanced transdermal delivery. Zetasizer® characterisation of three different formulations of curcumin nanoparticles (Cu-NPs) showed the size ranged from 167.3 ± 3.8 nm to 251.5 ± 5.8 nm, the polydispersity index (PDI) values were between 0.26 and 0.46 and the zeta potential values were positive (+ 18.1 to + 20.2 mV). Scanning electron microscopy (SEM) images supported this size data and confirmed the spherical shape of the nanoparticles. All the formulations showed excellent entrapment efficiency above 80%. FTIR results demonstrate the interaction between chitosan and sodium tripolyphosphate (TPP) and confirm the presence of curcumin in the nanoparticle. Differential scanning calorimetry (DSC) studies of Cu-NPs indicate the presence of curcumin in a disordered crystalline or amorphous state, suggesting the interaction between the drug and the polymer. Drug release studies showed an improved drug release at pH 5.0 than in pH 7.4 and followed a zero order kinetics. The in vitro permeation studies through Strat-M® membrane demonstrated an enhanced permeation of Cu-NPs compared to aqueous curcumin solution ( p ˂ 0.05) having a flux of 0.54 ± 0.03 μg cm −2 h −1 and 0.44 ± 0.03 μg cm −2 h −1 corresponding to formulations 5:1 and 3:1, respectively. The cytotoxicity assay on human keratinocyte (HaCat) cells showed enhanced percentage cell viability of Cu-NPs compared to curcumin solution. Cu-NPs developed in this study exhibit superior drug release and enhanced transdermal permeation of curcumin and superior percentage cell viability. Further ex vivo and in vivo evaluations will be conducted to support these findings.